2013
DOI: 10.1177/1753193413498547
|View full text |Cite
|
Sign up to set email alerts
|

Cubital tunnel syndrome: a comparison of an endoscopic technique with a minimal invasive open technique

Abstract: Both open and endoscopic methods for ulnar nerve decompression have been described. The purpose of this study is to compare the 6-month results of a minimal invasive open technique with an endoscopic technique. We treated 60 patients with unilateral ulnar neuropathy at the elbow, employing both techniques. Six months postoperative we found no differences in treatment effect on pain and disability scores between both groups, but both techniques resulted in an early postoperative relief of symptoms and good pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 14 publications
0
28
0
3
Order By: Relevance
“…Data from 3 studies 3,8,30 that compared ECTuR with OCTuR were pooled for meta-analysis. Analysis was done for 2 outcomes: (1) clinical improvement and (2) complications.…”
Section: Meta-analysismentioning
confidence: 99%
“…Data from 3 studies 3,8,30 that compared ECTuR with OCTuR were pooled for meta-analysis. Analysis was done for 2 outcomes: (1) clinical improvement and (2) complications.…”
Section: Meta-analysismentioning
confidence: 99%
“…12,13 When the main underlying cause of the secondary CuTS is heavy scarring, the objective of surgical intervention will be relieving compression, which is basically achieved either via formal open in situ decompression of the ulnar nerve with or without external/internal neurolysis throughout the entire cubital tunnel together with preserving neural vascularity or via more conservative endoscopic technique that would avoid more scarring. [13][14][15][16][17] However, in the authors' view, the formal open in situ decompression will be more suitable for the cases of both groups involved in this study due to the heavy tough scarring encountered in all cases that could not be amenable to release via endoscopic technique. Currently, the goals are expanded to include relieving compression neuropathy of the ulnar nerve and preventing postoperative adhesions, thus minimizing recurrence rate which puts the foundation for orthobiologic nerve insulators.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical treatments are recommended for patients who have not responded to non-surgical intervention that includes simple decompression, in which Osborne's band can be released using either open or endoscopic surgical methods, medial epicondylectomy, and anterior transposition of the ulnar nerve by intramuscular, submuscular, or subcutaneous placement of the nerve. Studies reported that no certain surgical method has encouraging outcomes, so in patients with an advanced stage of cubital tunnel syndrome, anterior transposition of the ulnar nerve should be considered as it can release the nerve and resolve the dynamic factors involved in cubital tunnel syndrome [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%